The Increase of Family’s Health Belief in Mental Disorder with Spiritual Approach - AH. Yusuf, NIDN. 0001016716 (TextRoad Publication, 2015)
Mental disorder is the problem with cognitive and mal-adaptive behavior. A family who have a member with mental disorder, will experience continually objective and subjective burden, serious stress for a lifetime, that cause ineffective family’s health belief and choice of treatment. The intervention in this study was to improve family’shealth belief with spiritual approach. This study was designed by pre-post test control group design.The population was every family of patient with mental disorder, lived in Surabaya, there are 13 persons in each group. Data analysis was done using paired t-test and independent t-test. This study showed that there was significant change in total of family’s health belief (p=0,004), significantly change in aspects of (1) perceptions about benefits (p=0,009), (2) perception about barriers(p=0,035) and perception about self efficacy(p=0,002). There was no significant changing in perception about susceptibility and severity (p=0,052). There was an increase of average difference between pre and post test among the treatment group, about 0,69, and about 0,47 among control group. Family therapy with spiritual approach can increase family’s health beliefaboutmental disorder